Prototype single-balloon enteroscopy with passive bending and high force transmission improves depth of insertion in the small intestine - Morita, Yasuhiro; Bamba, Shigeki; Inatomi, Osamu; Takahashi, Kenichiro; Imai, Takayuki; Murata, Masaki; Ohno, Masashi; Sasaki, Masaya; Tsujikawa, Tomoyuki; Andoh, Akira (Intestinal research, 2020)
Background/Aims: We retrospectively analyzed Crohn’s disease (CD) patients with small intestinal strictures who underwent single-balloon enteroscopy (SBE) to ascertain whether prototype SBEs with a passive bending mechanism and high force transmission insertion tube had better insertability in the small intestine than a conventional SBE.Methods: Among 253 CD patients who underwent SBE, we identified 94 CD patients who had undergone attempted endoscopic balloon dilatation (EBD) for small intestinal stenosis for inclusion in this study. We analyzed whether the type of scope used for their initial procedure affected the cumulative surgery-free rate. For the insertability analysis, patients who underwent SBE at least twice were divided into 3 groups according to the type of scope used: conventional SBE only, prototype SBE only, and both conventional and prototype SBEs. For each group, depth of insertion, procedure time, and number of EBDs were compared in the same patient at different time points.Results: The success rate of EBD was 88.3%. The 5- and 10-year cumulative surgery-free rate was 75.7% and 72.8%, respectively. Cox regression analysis indicated that the factors contributing to surgery were long stricture (≥2 cm), EBD failure, and elevated Crohn’s Disease Activity Index, but not the type of scope used for EBD. The prototype SBEs significantly improved the depth of insertion (P=0.03, Wilcoxon’s signed-rank test).Conclusions: In CD patients with small intestinal stenosis, the prototype SBEs with a passive bending mechanism and high force transmission insertion tube did not improve long-term EBD outcome but did improve deep insertability. (Clinical Trial Registration No. UMIN000037102)